Préparer des transparents avec Seminar - Goossens, M; Rahtz, S (GUTenberg association, 1994)
This article reviews the Seminar document class, which offers a user-friendly approach to the generation of transparencies with LaTeX. It allows you to manage it in an easy way your transparencies by letting you combined all LaTeX commands with more specific commands for defining their layout. Moreover, in combination with the PSTricks macros, Seminar becomes an even more performing tool for creating your transparencies.